Kinetics for Reduction of Iron Ore Based on the Phase Space Reconstruction - Guo-Feng Fan; Li-Ling Peng; Wei-Chiang Hong; Fan Sun (Journal of Applied Mathematics)
A series of smelting reduction experiments has been carried out with high-phosphorus iron ore of the different bases and heating rates by thermogravimetric analyzer. The derivative thermo gravimetric (DTG) data have been obtained from the experiments. After analyzing its phase space reconstruction, it is found that DTG phase portrait contains with a clear double “∞” attractor characteristic by one-order delay. The statistical properties of the attractor inside and outside the double “∞” structures are characterized with interface chemical reaction control and diffusion control stage in dynamic smelting process, respectively; the results are deserved to be a reference value on understanding of the mechanism and optimization and control of the process in smelting reduction of high-phosphorus iron ore.